Bibliometric analysis of the research on the impact of environmental regulation on green technology innovation based on citespace - Mingxing Li; Xinxing Wang; Zihao Wang; Babar Maqbool; Abid Hussain; Waris Ali Khan (MDPI, 2022)
With increasing environmental regulation (ER), the requirements for green technology innovation (GTI) in enterprises are also rising. However, there are relatively few systematic summaries of the themes of ER-affecting GTI. Adopting the method of bibliometrics and visual analysis, this research discusses the status of research and development trends of ER-affecting GTI and summarizes the research in this field. The paper takes 738 papers from 2001 to 2021 in the core database of Web of Science as the research sample. Based on CiteSpace, this paper makes a visual analysis of the number of published papers, institutions, authors, keywords, countries (regions) and journals. The study found that to some extent, favorable collaboration between authors and institutions in this field needs to be strengthened. Research hotspots in this field include innovation, technology, performance, policy and environmental regulation. Renewable energy consumption, the pollution haven hypothesis, sustainable development, carbon dioxide emission, energy technology and environmental Kuznets curve are the current research frontiers in this field. In terms of the number of published papers, research in this field has been conducted in a national (regional) layout with China as the core force, and Italy, America, Britain, Germany and other European countries as important forces. This field covers three main research areas: enterprise performance, policy instruments and research methods, going through the start-up phase (2001–2011), the growth phase (2012–2018) and the development phase (2019–2021). Future research can further incorporate the digital economy and synergy of multiple environmental regulation policies into this field, which will continuously enrich the theoretical research system in this field. The content, methods and conclusions of research in this field are becoming increasingly diverse.